Penerapan Media Video untuk Meningkatkan Pemahaman Mahasiswa Prodi Kependidikan Agama Buddha STABN Raden Wijaya - walyono; Budhi Setyo Darma (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2020)
This study aims to describe (1) student learning outcomes before using instructional video media, (2) student responses to the use of instructional video media, and (3) increase learning outcomes after using student learning videos. This research method is a survey method. The study population was students and lecturers majoring in Buddhist Religious Education. The sample of this research is the fourth-semester students majoring in Buddhist Education. Data collection techniques used include interviews, questionnaires, and tests. The results showed the average student learning outcomes before being given an action 76,20 (2) students' responses to the use of instructional video media 84% of students stated learning media videos were interesting and could increase understanding, and (3) average student learning outcomes after learning using instructional video media increased to 82.20 after using instructional video media.